Structural limits to sustainable development: managers and progressive agency. (18th November 2005) - Springett, Delyse
The 'contradiction' inherent in sustainable development has produced a discursive struggle between two paradigms. The 'business case' for sustainable development frames the concept as a narrative of eco-modernism that fails to contest the structural bases of unsustainability. The competing radical discourse constructs sustainable development as having emancipatory power to produce a more ecologically rational and socially just metanarrative, challenging the dominant model of economic rationality. Investigations in the area of innovation and sustainable development need to take account of this contestation that revolves around institutional and structural limits that have become normalised to the extent that they sometimes escape examination. This has implications for the awareness, education and level of agency of managers in capitalist organisations. A research inquiry conducted in New Zealand revealed that the 'business case' represented the major discursive formation around sustainable development, chiefly promoted by a coalition of government and business interests, although this model and the radical paradigm were both contested by neo-liberal groups. Corporate managers conceived the 'business case' as their chief means of exercising agency to negotiate the meaning of sustainable development in the workplace; although the research discourse opened up a conceptual space where counter-hegemonic positions addressing the structural limits to sustainable development and the limitations to the 'business case' began to emerge.